Heavy metal contamination and ecological-health risk assessment for the sediments of a tropical coastal lake, Southwest India - Vishnu Sagar M. K.; Mirsana S.; Sabu Joseph; Selvakumar S.; Sheela A. M.; Amit Kumar (Environmental Monitoring and Assessment, 2026)

Widespread Occurrence of Colletotrichum falcatum Pathotype CF13 in the Subtropical India Dictates Continuous Pathogenic Virulence and Severe Sugarcane Crop Destructions - R. Viswanathan; Sujeet Pratap Singh; R. Selvakumar; Chandramani Raj; Dinesh Singh; Y. P. Bharti; M. L. Chhabra; Anuradha Sharma; Md. Minnatullah; Rakesh Mehra; Harvinder Singh Yadav; Sanjay Kumar Goswami; et al. (Sugar Tech, 2025)

Enterobacter hormaechei mediated biodegradation of PET: a sustainable approach to plastic waste - Selvakumar Santhosh; Jayaraman Narenkumar; Kayeen Vadakkan; M. S. Nandini; Aruliah Rajasekar; Rajaram Rajamohan (Biodegradation, 2025)

Prospecting indigenous Bt isolates for bioinsecticidal efficiency against soil-borne white grub, Holotrichia serrata (F.) (Coleoptera: Scarabaeidae) - M. Manoj; K. Tamilvendan; Mohan Chavan; G. Selvakumar; K. Nagaraju; C. Manjunatha (Journal of Asia-Pacific Entomology, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Tackling toxicity and stability using eco-friendly metal-halide ion substituted perovskite nanocrystals for advanced display color conversion - Maithili K. Rao; M. Selvakumar; M.G. Mahesha; Selvaraj Paramasivam; M.S. Santosh; S. Senthilkumar; Shiva Kant; Sami Rtimi (Chemical Engineering Journal, 2024)

Quinoline-quinoline schiff-base as an effective chromogenic, fluorogenic, and smartphone assisted RGB detection of Pb2+ ion in near aqueous medium - Kathirvel R; Poongodi M; Vetriarasu V; Vivekanandan K.E; Selvakumar K; Sami Al Obaid; Arivalagan Pugazhendhi; Geetha Venkatesan (Environmental Research, 2024)

Development of superhydrophobic/superoleophilic cotton micro dust waste functionalized SiO2 nanocomposite as an efficient adsorbent for oil/water separation - A. Dhakshana; R. Selvakumar; K. Vivekanand; M. Alagappan; K. Chandraraj; S. P. Suriyaraj (Nanotechnology for Environmental Engineering, 2024)

First Report of Exserohilum rostratum Causing Sugarcane Leaf Spot in India - R. Selvakumar; M. Remya; R. B. Akshay Ravi; R. Viswanathan (Sugar Tech, 2023)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Environmental impact of one-step hydrothermal green synthesized ZnO nanoparticles in DI diesel engine performance analysis using duel fuel - S. Ganesan; S. lakshmisankar; Seepana Deepak; M. Selvakumar; S. P. Venkatesan; J. Hemanandh (Nanotechnology for Environmental Engineering, 2023)

Heterostructures of polyaniline and Ce–ZnO nanomaterial coated flexible PET thin films for LPG gas sensing at standard environment - D. Selvakumar; K.P. Sonu; G. Ramadoss; R. Sivaramakrishnan; R. Jayavel; M. Eswaramoorthy; K. Venkateswara Rao; A. Pugazhendhi (Chemosphere, 2023)

Recent advances in consolidated bioprocessing for conversion of lignocellulosic biomass into bioethanol – A review - Selvakumar Periyasamy; J. Beula Isabel; S. Kavitha; V. Karthik; Badr A. Mohamed; Desta Getachew Gizaw; P. Sivashanmugam; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2023)

Varietal Break Down to Red Rot in the Sugarcane Variety Co 0238 Mimics Vertifolia Effect: Characterizing New Colletotrichum falcatum Pathotype CF13 - R. Viswanathan; Sujeet Pratap Singh; R. Selvakumar; Dinesh Singh; Y. P. Bharti; M. L. Chhabra; B. Parameswari; Anuradha Sharma; Md. Minnatullah (Sugar Tech, 2022)

Effects of the COVID-19 pandemic on the environment, waste management, and energy sectors: a deeper look into the long-term impacts - Badr A. Mohamed; I. M. Rizwanul Fattah; Balal Yousaf; Selvakumar Periyasamy (Environmental Science and Pollution Research, 2022)

Chemical, physical and biological methods to convert lignocellulosic waste into value-added products. A review - Selvakumar Periyasamy; V. Karthik; P. Senthil Kumar; J. Beula Isabel; Tatek Temesgen; B. M. Hunegnaw; B. B. Melese; Badr A. Mohamed; Dai-Viet Nguyen Vo (Environmental Chemistry Letters, 2022)

Graphene-based materials for environmental applications: a review - V. Karthik; P. Selvakumar; P. Senthil Kumar; Dai-Viet N. Vo; M. Gokulakrishnan; P. Keerthana; V. Tamil Elakkiya; R. Rajeswari (Environmental Chemistry Letters, 2021)

Enzyme-loaded nanoparticles for the degradation of wastewater contaminants: a review - V. Karthik; P. Senthil Kumar; Dai-Viet N. Vo; P. Selvakumar; M. Gokulakrishnan; P. Keerthana; V. Audilakshmi; J. Jeyanthi (Environmental Chemistry Letters, 2021)

Spectroscopic Studies on the Interaction of Naphthyridines with DNA and Fluorescent Detection of DNA in Agarose Gel - G. Mahalakshmi; B. Selvakumar; K.N. Vennila; P. Lakshmana Rao; S. Madhuri; M. Seenivasaperumal; Kuppanagounder P. Elango (Journal of Fluorescence, 2021)

Are Tanycytes the Missing Link Between Type 2 Diabetes and Alzheimer’s Disease? - Sudhanshu P. Raikwar; Sachin M. Bhagavan; Swathi Beladakere Ramaswamy; Ramasamy Thangavel; Iuliia Dubova; Govindhasamy Pushpavathi Selvakumar; Mohammad Ejaz Ahmed; Duraisamy Kempuraj; Smita Zaheer; Shankar Iyer; Asgar Zaheer (Molecular Neurobiology, 2019)

Osmotolerant Cytokinin Producing Microbes Enhance Tomato Growth in Deficit Irrigation Conditions - Govindan Selvakumar; Gurupadam Hema Bindu; Ravindra M. Bhatt; Kaushal K. Upreti; Arogyanathan M. Paul; A. Asha; Kademani Shweta; Maryada Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Epidemiology of Fusarium Diseases in Sugarcane: A New Discovery of Same Fusarium sacchari Causing Two Distinct Diseases, Wilt and Pokkah Boeng - R. Viswanathan; C. G. Balaji; R. Selvakumar; P. Malathi; A. Ramesh Sundar; C. Naveen Prasanth; M. L. Chhabra; B. Parameswari (Sugar Tech, 2017)

Effects of Fluoride on Bone in an Animal Model of Vitamin D Deficiency - Joseph Dian Bondu; M. S. Seshadri; R. Selvakumar; Jude Joseph Fleming (Indian Journal of Clinical Biochemistry, 2017)

Design, Synthesis, Spectral Analysis, In Vitro Anticancer Evaluation and Molecular Docking Studies of Some Fluorescent 4-Amino-2, 3-Dimethyl-1-Phenyl-3-Pyrazolin-5-One, Ampyrone Derivatives - D. Premnath; Israel V. M. V. Enoch; P. Mosae Selvakumar; M. Indiraleka; J. Jannet Vennila (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Silk–PVA Hybrid Nanofibrous Scaffolds for Enhanced Primary Human Meniscal Cell Proliferation - Mamatha M. Pillai; J. Gopinathan; B. Indumathi; Y. R. Manjoosha; K. Santosh Sahanand; B. K. Dinakar Rai; R. Selvakumar; Amitava Bhattacharyya (The Journal of Membrane Biology, 2016)

A Highly Selective Fluorescent Sensor for Pb2+ Based on a Modified β-Cyclodextrin - Eva Janet Antony; Masilamani Raj; Rajathi Queen Paulpandi; Mosae Selvakumar Paulraj; Israel V. M. V. Enoch (Journal of Fluorescence, 2015)

Citricoccus zhacaiensis B-4 (MTCC 12119) a novel osmotolerant plant growth promoting actinobacterium enhances onion (Allium cepa L.) seed germination under osmotic stress conditions - Govindan Selvakumar; Ravindra M. Bhatt; Kaushal K. Upreti; Gurupadam Hema Bindu; Kademani Shweta (World Journal of Microbiology and Biotechnology, 2015)

Aquatic insect conservation: a molecular genetic approach - K. G. Sivaramakrishnan; S. Janarthanan; C. Selvakumar; M. Arumugam (Conservation Genetics Resources, 2014)

Effect of Biotin and Galactose Functionalized Gelatin Nanofiber Membrane on HEp-2 Cell Attachment and Cytotoxicity - R. Selvakumar; S. Nazar Mohamed Mohaideen; S. Aravindh; C. Sabarinath; M. Ananthasubramanian (The Journal of Membrane Biology, 2014)

Revealing effect of bathymetry over tsunami run-up through factor analysis - R. Selvakumar; S. M. Ramasamy (Arabian Journal of Geosciences, 2013)

Seven novel single nucleotide polymorphisms identified within river buffalo (Bubalus bubalis) lactoferrin gene - Periasamy Kathiravan; Ranjit S. Kataria; Bishnu P. Mishra; Praveen K. Dubey; M. Selvakumar; Neetu Tyagi (Tropical Animal Health and Production, 2010)

Control of sheath blight disease in rice by thermostable secondary metabolites of Trichothecium roseum MML003 - M. Jayaprakashvel; M. Selvakumar; K. Srinivasan; S. Ramesh; N. Mathivanan (European Journal of Plant Pathology, 2010)

Thyroid autoantibody measurement by enzyme immunoassay - D. Charles Stephen; Nihal Thomas; R. Selvakumar; M. S. Seshadri; A. S. Kanagasabapathy (Indian Journal of Clinical Biochemistry, 1997)